PENGARUH UKURAN DEWAN KOMISARIS, KOMITE AUDIT DAN FAKTOR LAINNYA TERHADAP MANAJEMEN LABA - LIUS SUARDIKA IDRIS; Kartina Natalylova (E-Jurnal Akuntansi TSM, 2021)
The objective of this research is to obtain evidence about the influence of size commissioner on board, audit committee, leverage, profitability, firm size, firm growth, firm age, and audit quality to earnings management. This research used companies that listed in non-financial sector in Indonesia Stock Exchange during 2017-2019 as the population. There are 194 companies meet the criteria by using purposive sampling method. The results of this study indicate that profitability, firm growth, and audit quality affect earnings management, that earnings management practices will be higher because the demands of good prospect reports in the public make companies with high growth motivated to carry out earnings management. However the size of the board of commissioners, audit committee, leverage, firm size, and firm age have no effect so earnings management.